Descriptions of new gynandromorphs of Xylocopa augusti Lepeletier (Hymenoptera: Apidae: Xylocopini) from Argentina - Almada, Valentín (2022)
Gynandromorphs are individuals that display both male and female features throughout the body and are rarely found in nature. We document and describe two new gynandromorphs of the large carpenter bee Xylocopa (Neoxylocopa) augusti reared from a trap-nest in La Plata, Buenos Aires, Argentina. In addition, based on a literature review, we assessed the frequency of the different types of gynandromorphs, and the body part affected, among large carpenter bees. Both gynandromorphs were assigned to the mixed category, the most common category reported in the literature (22 of 25 specimens). The remaining three specimens exhibit a bilateral pattern in all tagmata. The presence of both sexes’ secondary sexual characteristics occurred more frequently on the mesosoma than on the head or metasoma. Trap nests used in bee hotels promote the conservation and study of wild bees and might facilitate the discovery of rare cases of gynandromorphs that would remain unknown otherwise under normal nesting conditions in the wild.